KELAYAKAN FINANSIAL USAHA BUDIDAYA RUMPUT LAUT (Kappaphycus alvarezii) TERDAMPAK PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA UAP (PLTU) PUNAGAYA DI KECAMATAN BANGKALA, KABUPATEN JENEPONTO - Tetty, Tetty; Khairunnisa, Khairunnisa; Haidawati, Haidawati (MarIslands, 2021)
Development PLTU Punagaya raises concerns on survival growers seaweed cultivation in the Punagaya Village, because of the hot water drainage directly to the seaweed cultivation. The research aimed to assess the financial feasibility of the seaweed cultivation business. The research method used to R / C Ratio and BEP analysis. The results showed although income decreased, seaweed cultivation business still feasible criteria